2009
DOI: 10.1159/000233247
|View full text |Cite
|
Sign up to set email alerts
|

Ribose Treatment Reduced the Infarct Size and Improved Heart Function after Myocardial Infarction in Rats

Abstract: Objective: In this study the effect of ribose on heart function and infarct-size was analyzed 6 h after myocardial infarction (MI) in rats. Methods: Continuous i.v.-infusion of NaCl or ribose (200 mg/kg/h) was started one day prior to induction of MI in female Sprague-Dawley rats which was done by ligation of the left coronary artery. Six hours after MI heart function was measured with 3F tip catheter, cardiac output by thermodilution method. Thereafter the ischemic area was delineated by Evans Blue infusion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Furthermore, when D-ribose supplementation was provided pre-infarction, Gonzales et al reported in adult rats that there was a significant reduction in the area of the left ventricular infarct, as well as a significant improvement in left ventricular function when assessed at six hours post-infarct. Left ventricular systolic pressure and contractility were restored to normal levels with a significant improvement in left ventricular relaxation when supplementing with D-ribose [ 19 ].…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, when D-ribose supplementation was provided pre-infarction, Gonzales et al reported in adult rats that there was a significant reduction in the area of the left ventricular infarct, as well as a significant improvement in left ventricular function when assessed at six hours post-infarct. Left ventricular systolic pressure and contractility were restored to normal levels with a significant improvement in left ventricular relaxation when supplementing with D-ribose [ 19 ].…”
Section: Reviewmentioning
confidence: 99%